PENGAWASAN UNTUK PEMBERANTASAN KORUPSI - Umar, Haryono (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2012)
The role of control is vital in ensuring the proper financial and performance accountabilityreport. Control is the systematic effort to set performance standards with planning objectives, todesign information feedback systems, to compare actual performance with these predeterminedstandard, to determine whether there are any deviations and to measure their significance, and totake any action required to assure that all corporate resources are being used in the effective andefficient way possible in achieving corporate objective. Auditing is a tool for implementingcontrol. Auditing is a systematic process of objectively obtaining and evaluating evidenceregarding assertations about economic actions and events to ascertain the degree ofcorrespondence between these assertations and established criteria and communicating theresults to interested users. Audit is an examination that provides an objective and constructiveassessment of the extent to which financial, human and physical resources are managed with dueregard to economy, efficiency and effectiveness; and accountability relationships are reasonableserved. Audit contributes in corruption combat strategy. State losses could be found out byimplementing an effective audit such as forensic audit, investigative audit or other types ofauditing. Corruption is â€œthe misuse of public office for private gain.â€ As such, it involves theimproper and unlawful behavior of public-service officials, both politicians and civil servants,whose positions create opportunities for the diversion of money and assets from government tothem and their accomplices. One of corruption example is fraud. fraudulent financial reporting asintentional or reckless conduct, whether act or omission, that results in materially misleadingfinancial statements. Auditor should find out and report this criminal activities as told by theauditing standards. This paper analyzes the audit role in combating corruption in Indonesia.